PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA SURYA DI WADUK CIRATA, KABUPATEN PURWAKARTA - Asep Hidayat; Sekar Agnia Ramdani; Siti Latifah Romadhoni (Jurnal Inovasi Penelitian, 2022)
The general objective of the research is to review the process of the ongoing construction of a Solar Power Plant (PLTS) in Cirata Reservoir, Purwakarta Regency. This study uses a descriptive research method with a qualitative approach. This study concludes that the construction of PLTS Floating in Cirata has been quite effective in the development process. The construction of the Cirata Floating PLTS will begin in 2020 and the first phase of the PLTS construction will be completed at the end of 2021 with a target of 50 megawatts (MW), while the rest will be continued in 2022